Genome-wide analysis of bHLH transcription factor family reveals their involvement in kernel development and biotic stress responses in Chinese chestnut - Li, Rongchen; Huang, Liyun; Huang, Xiaolu; Liao, Jianming; Wei, Xiaojuan; Li, Junji; Zeng, Guangyu; Shi, Zhuogong; Zhang, Jingzheng; Zhao, Zhiheng (Frontiers in Plant Science, 2025)
IntroductionThe basic helix-loop-helix (bHLH) transcription factor family plays crucial roles in plant growth, development, and responses to environmental stresses. However, a systematic characterization of bHLH genes in Castanea mollissima has been lacking.MethodsWe performed a genome-wide identification of bHLH genes in C. mollissima, followed by phylogenetic, structural, motif, chromosomal distribution, and cis-element analyses. Co-expression network analysis and transcriptomic profiling under Dryocosmus kuriphilus infestation were conducted, and representative genes were validated using qRT-PCR across seed developmental stages.ResultsA total of 124 non-redundant bHLH genes (CmbHLHs) were identified and classified into eight subfamilies, consistent with conserved gene structures and motif compositions, particularly motif-1 and motif-2 of the canonical bHLH domain. Chromosomal mapping revealed non-random distribution and tandem duplication events. Promoter analysis indicated enrichment of cis-elements responsive to stress, hormone signaling, and developmental regulation. Co-expression analysis highlighted hub genes, including CmbHLH82 and CmbHLH57, with potential regulatory functions. Transcriptomic data showed that most CmbHLHs were downregulated under D. kuriphilus infestation, notably CmbHLH63 and CmbHLH51. qRT-PCR confirmed the dynamic expression of five selected genes during seed development.DiscussionThese findings provide the first comprehensive overview of the bHLH gene family in Chinese chestnut. The results highlight candidate genes potentially involved in development and insect resistance, thereby laying a foundation for future functional and breeding studies.